A comparative study of film and series tourism locations in European destinations - Andrea, Szőllős-Tóth; Zoltán, Zoltán; Csapóné Riskó, Tünde (Studia Mundi – Economica, 2025)
In the wake of the restrictions imposed by the coronavirus outbreak, the issue of overtourism has once again come to the fore. The study focuses on destinations that have experienced a notable increase in visitor numbers following the popularity of a film or series filmed there. A case study of three European film and series tourism destinations is presented in order to identify the indications of overtourism. The inhabitants of Dubrovnik, Hallstatt and the two islands of the Sporades (Skopelos and Skiathos) are confronted with a range of challenges associated with the presence of tourists, including congestion, overloaded infrastructure, rising food and property prices, and high environmental pressures. A number of measures have been identified which could assist the municipalities. These include the promotion of public transport as an alternative to private vehicles, with the aim of reducing the environmental impact; the regulation of the mooring of cruise ships and other strategies for managing visitor numbers; and the introduction of online ticketing and advance booking, which could bring significant benefits for visitors and destination management. In order to mitigate the adverse effects of a sudden surge in popularity, destinations that have become well-known due to their cinematic or televisual associations must implement a well-considered tourism strategy. This should entail optimising the number of tourists in the area through a conscious development of attractions.
Keywords: film tourism; movie tourism; shooting location; film location; tourism destination; overtourism